Good Girls, Bad Girls: The Enduring Lessons of Twelve Women of the Old Testament - Wray, T. J. (Rowman & Littlefield Publishers, 2008)
The few popular Bible stories about women are often presented in black and white—the women were good or bad, Ruth or Jezebel. But most of us fall somewhere in between these two extremes. Good Girls, Bad Girls invites readers to take a more nuanced look at 12 women in the Old Testament, to explore their lives more deeply in historical context, and to grasp what these stories might mean to women today. T. J. Wray, a biblical scholar, asks readers to consider whether Jezebel was really as bad as generally believed, and includes women ranging from the infamous Delilah to the mysterious Witch of Endor. Impeccably researched and beautifully written, Good Girls, Bad Girls will appeal to both individual readers and groups interested in learning what the Bible really has to say about these twelve important women.